Policing and the Police Function: What’s in a name? - Joery Matthys (Nordicum-Mediterraneum)
This article calls for a renewed focus on the general assistance duties engrained in community policing, which brings the police officer into closer contact with the citizen. In this perspective, the essence of police work is to make society safer by tackling social problems. This supposes a number of preconditions. At the micro level, police training must be strengthened, so that competences like abstract thinking become more central. At the meso level, the connection between the police and other organizations that play a role in tackling current social issues must be improved. At the macro level, smart investments must be made in both the security domain and in related policy domains, such as health and poverty reduction. This is in line with the a shift towards a neo-Weberian perspective, where the government is more central in tackling social problems, without returning to a bureaucratic and strictly hierarchical way of thinking.